Beatrice: A Study in the Creation and Destruction of Value - Baker, George P. (Journal of Finance, 1992)
This paper chronicles the history of the Beatrice company from its founding in 1891 as a small creamery, through its growth by acquisition into a diversified consumer and industrial products firm, and its subsequent leveraged buyout and sell-off. The paper analyzes the value consequences the firm's acquisition and divestiture policies, its organizational strategy, and its governance. The analysis sheds light on a number of issues in organization theory, strategy, and corporate finance, including the sources of value in diversifying aquisitions, the cost of over-centralization and weak corporate governance, and the mechanisms of value creation in the market for corporate control.